THE INFLUENCE OF ENVIRONMENTAL CHARACTERISTICS AND SERVICE QUALITY ON REVISIT INTENTION IN CULINARY TOURISM (WISKUL) IN KAB. KOLAKA - Satria, Joshua Febri; Titing, Andry Stepahnie; Ismanto, Ismanto Ismanto (Jurnal Ekonomi Manajemen, 2023)
The purpose of this study was to determine the effect of Environmental Characteristics and Service Quality on Revisit Intention on Culinary Tourism (WISKUL) in Kolaka Regency. This research is survey research using a questionnaire as an instrument. The population in this research were all customers who had visited Culinary Tourism (WISKUL) in Kolaka Regency and 110 respondents were taken using a purposive sampling technique. Data collection techniques are primary data and secondary data. The data obtained were analyzed using PLS analysis techniques through the Smart PLS software. Based on the results of this study, it shows that Environmental Characteristics and Service Quality have a positive and significant effect on Revisit Intention on Culinary Tourism (WISKUL) in Kolaka Regency. Greater influence by Environmental Characteristics which shows that the intention to return is influenced by several factors of Environmental Characteristics, namely employees who are friendly and responsive in providing services and having an attractive place, as well as comfortable interior (indoor) and exterior (outdoor) settings so that visitors feel comfortable to make revisit intention.